Analysis of recent operational events involving inappropriate actions: influencing factors and root causes. (December 2021) - Podofillini, Luca; Reer, Bernhard; Dang, Vinh N.
Highlights: Modern digitalization, computer aids and automation change human-system interaction. HRA to improve treatment of cognition failures leading to inappropriate decisions. CESA-Q factor framework to analyze and quantify decision failures. CESA-Q validity demonstrated on recent operational events (2000–2016). Inappropriate decisions mostly due to procedures, HMI, experience and training. Abstract: The Human Reliability Analysis (HRA) of inappropriate actions (Errors Of Commission, EOCs) still suffers from technical gaps, especially for actions with decision-related motivations. Traditional, factor-based HRA methods often fail to address these motivations. Holistic analyses frameworks have been developed (namely, ATHEANA and MERMOS), but these rely on strong analyst expertise and require large efforts to make analyses traceable. This paper presents the application of the factor framework underlying the quantification module of the Commission Error Search and Assessment (CESA-Q) method. The framework is applied to fourteen operational events from the period 2000–2016, not used for the factor framework development. This gives the chance to confirm the validity of the CESA-Q factor framework to represent adequately the diverse situations influencing inappropriate decisions in real operational events. In the majority of the events, the triggering condition for the inappropriate decision is the information available to the operators, typically the procedural guidance, Human-Machine Interface, experience and training. In these cases, the dominant influencing factors (positively and negatively) identified through the CESA-Q analysis relate to verification of appropriateness of the decision. For another set of events, the inappropriate decision was driven by the prospect of other benefits (e.g. simplifying the plant control).